We have the right angle triangle with sides a, b, and c.

c is the hypotenuse, then:

c^2 = a^2 + b^2

43^2 = a^2 + 6^2

1849 = a^2 + 36

==> a^2 = 1849 -36

==> a^2 = 1813

==> a = sqrt1813 = 42.6 (approx.)

###### To do this, you need to use the Pythagorean theorem. If you remember, this theorem can be stated as A squared + B squared = C squared where C is the hypotenuse and A and B are the legs of the right triangle. So what we need to do is this:

A^2 + 6^2 = 43^2. Now we just do the math.

A^2 + 36 = 43^2

A^2 + 36 = 1849

A^2 = 1813

A = square root of 1813

The square root of 1813 is (rounded to the nearest 10th) 42.6.

So the two legs of the triangle are 42.6 and 6 and the hypotenuse is 43.